Evaluation the levels of Plasma Interleukins (IL-8, IFN-?, IL-10) in Preeclamptic Pregnancies (Baghdad Science Journal, 2011)
This study is to evaluate plasma levels of several cytokines in preeclamptic pregnancies compared to those of healthy pregnancies.Ninety pregnant women with preeclampsia (37 mild & 53 severe) and thirty healthy pregnant women were enrolled in the study. Blood samples were taken and plasma levels of IL-8, IL-10, and IFN-? were measured by enzyme-linked immunosorbent assay (ELISA).Preeclamptic women and their severe cases but not mild cases had significantly (P